Pleiotropic Ankyrins: Scaffolds for Ion Channels and Transporters - Sharon R. Stevens; Matthew N. Rasband (Taylor & Francis Group, 2022)
The ankyrin proteins (Ankyrin-R, Ankyrin-B, and Ankyrin-G) are a family of scaffolding, or membrane adaptor proteins necessary for the regulation and targeting of several types of ion channels and membrane transporters throughout the body. These include voltage-gated sodium, potassium, and calcium channels in the nervous system, heart, lungs, and muscle. At these sites, ankyrins recruit ion channels, and other membrane proteins, to specific subcellular domains, which are then stabilized through ankyrin's interaction with the submembranous spectrin-based cytoskeleton. Several recent studies have expanded our understanding of both ankyrin expression and their ion channel binding partners. This review provides an updated overview of ankyrin proteins and their known channel and transporter interactions. We further discuss several potential avenues of future research that would expand our understanding of these important organizational proteins.